Unusual new phenylethanoid and phenylpropanoid diglycosides from the leaves of Chloranthus spicatus (Thunb.) Makino. (September 2016) - Wang, Kui-Wu; Zhou, Man-Qing; Gu, Qin; Auckloo, Nazia Bibi; Wu, Xiao-Dan; Wu, Bin
Graphical abstract: Highlights: Two new diglycosides (1–2) and two known glycosides were reported. Their structures were identified by NMR spectra and HR-ESI–MS. First report of glycoside from Chloranthus spicatus . 1 and 2 showed potent tyrosinase inhibitory activities with IC50 of 15.4 μM and 29.1 μM. Abstract: Chloranthus spicatus (Thunb.) Makino (Chloranthaceae) has been used to treat aches, trauma, and bleeding in Traditional Chinese Medicine. Phytochemical investigation of the leaves of this plant led to the isolation an unusual new phenylethanoid diglycoside, spicaoside (1 ), and a new phenylpropanoid diglycoside, 1-allyl-3-methoxy-4- [apiofuranosyl(1 → 2)-glucopyranosyloxybenzene] (2 ), along with two known sesquiterpenoid glycosides, chloranoside A (3 ) and chloranthalactone E 8- O -β-d -glucopyranoside (4 ). Their structures were established by spectroscopic means. New compounds1 and2 showed moderate tyrosinase inhibitory activities with the IC50 value of 15.4 μM and 29.1 μM. This study represents the first report of glycoside from C. spicatus .